Dancing With Health: Quality of Life and Physical Improvements From an EU Collaborative Dance Programme With Women Following Breast Cancer Treatment - Karkou, Vicky; Dudley-Swarbrick, Irene; Starkey, Jennifer; Parsons, Ailsa; Aithal, Supritha; Omylinska-Thurston, Joanna; Verkooijen, Helena M.; van den Boogaard, Rosalie; Dochevska, Yoanna; Djobova, Stefka; Zdravkov, Ivaylo; Dimitrova, Ivelina; et al. (Frontiers in Psychology, 2021)
Background Women’s health has received renewed attention in the last few years including health rehabilitation options for women affected by breast cancer. Dancing has often been regarded as one attractive option for supporting women’s wellbeing and health, but research with women recovering from breast cancer is still in its infancy. Dancing with Health is multi-site pilot study that aimed to evaluate a dance programme for women in recovery from breast cancer across five European countries. Methods A standardised 32-hour dance protocol introduced a range of Latin American dances presented within a sports and exercise framework with influences from dance movement therapy. Fifty-four women (M age 53.51; SD 7.99) participated in the study who had a breast cancer diagnosis < three years, chemotherapy > 6 weeks, no indication of metastasis, or scheduled surgery/chemotherapy/radiation treatment for the duration of the intervention. Primary outcome data was collected for anthropometric and fitness measures next to cancer-related quality of life. T-tests and Wilcoxon signed ranked tests were used to establish differences pre and post intervention. Cohen’s d was also calculated to determine the effect size of the intervention. Results Statistically significant changes were found for: (i) weight, right and left forearm circumference and hip; (ii) 6-minute walking, right and left handgrip, sit-to-stand and sit-and-reach; (iii) the EORTC-QLQ C30 summary score as well as the subscales of emotional and social functioning and symptoms. In all cases the direction of change was positive, while Cohen’s d calculated showed that the effect of the intervention for these parameters ranged from intermediate to large. Conclusion Changes on the above anthropometric, fitness and quality of life measures suggest that the intervention was of value to the participating women recovering from breast cancer. Results also advocate collaborative efforts across countries to further research.